Resolving the Willingness-to-Pay Paradox: A Pricing Justice Perspective on Destination Loyalty in Emerging Tourism Contexts - Susanto, Eko; Modupe, Ajayi Olubunmi (Integrasi Sains Media, 2025)
Traditional tourism pricing models often fail to explain the